Otomatisasi Alat Sortir Ukuran Benih Kentang G - Nol Berbasis Load Cell - Anjani, Ayu Sri; Sihab, Hasbi Hasidik; Nurlaela, Intan; Fahmi, Muhammad Rusdan; Srimurni, Rafika Ratik; Nugroho, Iwan Satriyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to design an automatic seed sorting device for G-0 potato seeds using a load cell sensor as a solution to the limitations of manual sorting systems commonly used in the field. The system detects the seed weight through a load cell sensor connected to an Arduino microcontroller, enabling precise and automated sorting. The Exponential Comparison Method (MPE) was applied to evaluate four design alternatives based on functional, technical, and operational criteria. The results indicate that Design B is the most optimal, achieving the highest preference score. Financial feasibility analysis further supports the project's viability, with positive NPV, a high IRR, a B/C Ratio above 1, a short payback period, and a low break-even point. Therefore, the tool is considered feasible both technically and economically and shows strong potential for broader implementation in the agricultural sector.